Redescription and placement of Wyeomyia rorotai Senevet, Chabelard & Abonnenc (Diptera: Culicidae) in the subgenus Decamyia based on morphological and molecular analyses - Ribeiro, Paulino Siqueira; Galvão, Cleber; Talaga, Stanislas; Carinci, Romuald; Pavan, Márcio Galvão; Lourenço-De-Oliveira, Ricardo; Motta, Monique De Albuquerque (Zootaxa, 2020)
Decamyia Dyar is a subgenus of Wyeomyia Theobald with three valid species. Wyeomyia rorotai Senevet, Chabelard & Abonnenc, a species originally described rather briefly in the subgenus Dendromyia, is without subgeneric position in the genus. In the present work, we redescribe Wy. rorotai in all life stages and formally define its taxonomic placement in the subgenus Decamyia by combining morphological and molecular analyses based on the mitochondrial cytochrome c oxidase subunit I gene. We also show that Decamyia is a rather homogeneous group of four species, i.e. Wy. ulocoma (Theobald), Wy. pseudopecten Dyar & Knab, Wy. felicia Dyar & Núñez Tovar and Wy. rorotai, the immature stages of which almost exclusively inhabit the flower bracts of Heliconiaceae.